Effect of Supplementing Rice Bran and Wheat Bran with Probiotics on Growth Performance of Khari Kids - Pudasaini, Ramchandra; Dhital, Bigya (International Journal of Applied Sciences and Biotechnology, 2017)
An experiment was conducted in IAAS, Livestock Farm, Rampur Chitwan, Nepal in order to assess the growth performance of kids feeding diets supplemented with probiotics. The experiment was laid out in Randomized Complete Block Design (RCBD) with four replications and five feeding supplemented diets with probiotics treatments. Parameters studied were live weight gain, body measurements and economic analysis. The result of this study showed the highest cumulative mean live weight (13.24 kg) in the treatment group feeding mixture of rice bran and wheat bran with probiotics. Fortnightly and daily body weight gains were also highest in the treatment group having mixture of rice bran and wheat bran with probiotics. The highest (11.74cm) overall mean monthly heart girth was observed in the treatment group feeding mixture of rice bran and wheat bran with probiotics. The mean monthly cumulative neck girth, body length and wither height of kids did not differ significant (p>0.05) among treatments. However, the highest overall mean monthly cumulative neck girth (6.71cm), wither height (10.14cm) and body length (14.62cm) was observed in probiotics supplemented treatment groups. Highest (1.61) benefit cost ratio was obtained from goats reared on feeding mixture of rice bran and wheat bran with Probiotics and lowest (1.008) in wheat bran without probiotics. The result of the study thus suggests that feeding of rice bran and wheat bran with probiotics is beneficial in terms of growth rate and cost of production.Int. J. Appl. Sci. Biotechnol. Vol 5(4): 430-433